Knowledge of Cotton Growers about Integrated Weed Management Practices - A.T. Barkade , K.T.Lahariya , N.R. Koshti and D. M. Mankar, (Indian Journal of Extension Education, 2017)
The present study was undertaken in Karanja and Manora Panchayat Samitis of Washim district in Vidarbha region ofMaharashtra State. The findings revealed that majority of respondents belonged to middle age group ; educated up tocollege level; had middle family size (4 to 6 members), belonged to semi-medium size land holding category andagriculture was the main occupation, with annual income between of ` 1,00,001 to 2,00,000, had bi-seasonalcropping system, put up to 1.01 to 2.00 ha area under cotton crop; had medium sources of information; had mediumcategory of extension contact; had medium level of economic motivation;, had medium level of knowledge andadoption of integrated weed management practices. As regards the correlation analysis, independent variables namelyeducation, land holding, annual income, cropping pattern, area under cotton crop, sources of information, extensioncontact and economic motivation showed a positive and highly significant correlation with knowledge of therespondents at 0.01 level of probability. Whereas, the characteristics such as age, family size, occupation had shownnegative and non contributory effect with knowledge of the respondents.